Cardiac surgeryLeft atrial appendage stapling during totally thoracoscopic ablation of long-standing lone persistent atrial fibrillation – lessons learnt - Witkowska, Anna; Smoczyński, Radosław Hugon; Drobiński, Dominik; Kosior, Dariusz; Sypuła, Sławomir; Niewińska, Monika; Kaliciński, Zygmunt; Szafron, Bartłomiej; Świstowski, Jarosław; Suwalski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: The left atrial appendage (LAA) is considered to be the main site of thrombus formation in patients with atrial fibrillation (AFib). It is found in approximately 1.6-2.1% of patients undergoing ablation. Many techniques are introduced to reduce the risk of thromboembolic complications in patients with AFib. Aim of the study : Here we describe the totally thoracoscopic technique of LAA exclusion during ablation for lone persistent atrial fibrillation. Material and methods : 19 patients (12 men, 7 women) admitted to our department between November 2011 and February 2013 with lone persistent and long-standing persistent AFib underwent totally thoracoscopic ablation with LAA stapling. Mean age, AFib duration, EuroSCORE II, CHA2DS2-VASc score, left atrial dimension and LVEF were 57.8 (±11) years, 52.6 ±50 months, 0.67 ±0.2%, 1.5 ±1.3, 41 ±63 mm and 63.7 ±6.5%, respectively. One patient (5.8%) experienced prior stroke. All patients underwent transesophageal echocardiogram before the operation to rule out thrombus in the LAA. LAA exclusion was performed with the novel Tri-Staple stapler (Covidien, Mansfield, USA). Results: All but one patient (95%) were eligible for LAA stapling. The procedure took only a few minutes. We did not observe early or late bleeding from the stapler line. We had one case of bleeding from the left atrial wall in connection with LAA stapling successfully treated surgically. In transthoracic echocardiography we obtained confirmation of complete LAA exclusion with smooth endocardium. No incidence of stroke/TIA in follow-up was noted. All patients are alive. Conclusions : In our experience totally thoracoscopic LAA stapling is feasible and safe when done with caution and proper use of the stapler.